Informal Employment in Russia: Measurement, Scale and Dynamics - СинявскаяОксана Вячеславовна (Journal of Economic Sociology, 2010)
There are many approaches towards informal employment, including different ways of its determination, measurement and interpretation of its nature. This paper gives another approach to define and estimate the informal employment. The paper discusses the results of its scale assessments and its main characteristics that were received with the help of secondary analysis of the population survey conducted within the project on middle classes of the Moscow Carnegie Center*. It is the first time when the issue of dynamics and stability of individual status is raised. It was possible to investigate the dynamics due to the panel data of RLMS. The paper ends by the discussion of the nature of Russian informal employment and its possible development in the future. *The Carnegie Moscow Center ceased its work in the Russian Federation by order of the Ministry of Justice. Recognized as a foreign agent.